Systemic Analysis of a Novel Coxsackievirus Gene Delivery System in a Mouse Model - Kim, Y.J., The Catholic University of Korea, Bucheon, Republic of Korea; Yun, S.H., Sungkyunkwan University, Seoul, Republic of Korea; Lim, B.K., Sungkyunkwan University, Seoul, Republic of Korea; Park, K.B., The Catholic University of Korea, Bucheon, Republic of Korea; Na, H.N., The Catholic University of Korea, Bucheon, Republic of Korea; Jeong, S.Y., The Catholic University of Korea, Bucheon, Republic of Korea; Kim, D.S., The Catholic University of Korea, Bucheon, Republic of Korea; Cho, Y.J., The Catholic University of Korea, Bucheon, Republic of Korea; Jeon, E.S., Sungkyunkwan University, Seoul, Republic of Korea; Nam, J.H., The Catholic University of Korea, Bucheon, Republic of Korea (Journal of microbiology and biotechnology, 2009)
In order to systemically investigate the possibility of using coxsackievirus B3 (CVB3) to deliver foreign genes in vivo, a recombinant strain of CVB3 encoding the renilla gene (CVB3-renilla) was constructed. The recombinant CVB3 resulted in extensive and transient expression of the renilla protein within mouse organs, especially the pancreas. The level of expression was generally dependent upon the viral titer present. Moreover, the CVB3-renilla strain was completely attenuated. Interestingly, the recombinant CVB3 vector was expressed much more strongly in mouse organs than was a comparable adenoviral vector. The CVB3-renilla strain did not express the renilla gene in mice with pre-existing coxsackievirus-specific neutralizing antibodies, but direct organ-specific administration of the virus during open-peritoneum surgery was able to circumvent this immunity. This coxsackievirus vector may represent a useful means for delivering and expressing foreign genes in mouse models in an acute and extensive fashion.